Analysis of Optimal Capital Structure of Liquors Sub-Sector Companies Listed on the IDX - Sodikin, Sodikin; Heikal, Jerry (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study focus on the WACC method in determining the optimal cost of capital. The cost of capital must be calculated on an after-tax basis, because after-tax cash flow is the most relevant cash flow to fulfill an investment decision. This study aims to calculate the amount of WACC juxtaposed with the amount of ROA in liquors sub-sector companies listed on the IDX in the period 2018 - 2022 (DLTA and MLBI). The results showed the following calculation as follow: DLTA's highest ROA occurred in 2019 at 2,229%, but in the same year the WACC figure showed 4.44%, CAPM 4.46%, Equity/asset 85.10%, while in the period 2018 - 2022 the lowest WACC was in 2021 at 2.75%. And for MLBI, the highest ROA is 4.236% occurred in 2018, with WACC value 4.39%, CAPM 9.36%, and Equity/asset 40.41%. Meanwhile, the lowest WACC calculation occurred in 2020 at 3.23%. Thus it can be concluded that both of the companies have not achieved optimal result, because when the company achieved the highest ROA it was not matched by the lowest WACC in that period.